2023
DOI: 10.3390/membranes13050472
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids as Inducers of Protonophore and Ionophore Permeability of Biological and Artificial Membranes

Abstract: It is now generally accepted that the role of bile acids in the organism is not limited to their participation in the process of food digestion. Indeed, bile acids are signaling molecules and being amphiphilic compounds, are also capable of modifying the properties of cell membranes and their organelles. This review is devoted to the analysis of data on the interaction of bile acids with biological and artificial membranes, in particular, their protonophore and ionophore effects. The effects of bile acids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…This raises cytosolic Ca 2+ activity and ultimately causes eryptosis, the suicidal death of erythrocytes marked by the exposure of phosphatidylserine on the cell surface [65,66]. It was demonstrated that bile salt-associated hemolysis is partially calcium-mediated [66,67]. Moreover, the bile acid concentrations needed to induce eryptosis are greater than those needed to cause hemolysis [65].…”
Section: Discussionmentioning
confidence: 99%
“…This raises cytosolic Ca 2+ activity and ultimately causes eryptosis, the suicidal death of erythrocytes marked by the exposure of phosphatidylserine on the cell surface [65,66]. It was demonstrated that bile salt-associated hemolysis is partially calcium-mediated [66,67]. Moreover, the bile acid concentrations needed to induce eryptosis are greater than those needed to cause hemolysis [65].…”
Section: Discussionmentioning
confidence: 99%